Left heart function and strain for predicting change in hemoglobin levels in pediatric kidney transplantation recipients - Yue, Shufan; Xiao, Fei; Fan, Rui; Li, Wei; Liu, Donghong; Yao, Fengjuan; Lin, Hong; Wu, Chenglin; Liu, Longshan; Wang, Changxi; Li, Jun; Li, Cuiling (Frontiers in pediatrics, 2025)
Anemia is prevalent after kidney transplantation (KTx) and is associated with reduced graft survival. The associations between temporal changes in hemoglobin (Hb) level in the early posttransplant period with left ventricular (LV) and atrial (LA) function and strain are unknown. The study cohort included 71 successful pediatric KTx recipients between January 2021 and September 2022. Echocardiography was used to evaluate the cardiac structure, function, and strain both before and after KTx. Temporal changes in Hb values within 6 months after KTx were evaluated. According to the LV mass index (LVMI), recipients were divided into a left ventricular hypertrophy (LVH) group and a non-LVH group. Before KTx, the LVH group had a lower level of Hb and a higher incidence of anemia than the non-LVH group. However, this difference between the groups disappeared after KTx. Changes in Hb were faster in the LVH group than in the non-LVH group. There was a negative association between the absence of an Hb increase and diastolic blood pressure, the LVMI, early diastolic mitral annulus velocity to early diastolic filling wave ratio (E/E'), and the left atrial emptying volume index (LAEVI), while there was a positive association between LV ejection fraction (LVEF), LV global longitudinal strain, and LA strain. The LVMI and changes in LVEF showed a negative correlation, whereas changes in the LAEVI showed a positive correlation with the absence of Hb increase during the early period after KTx. Children with LVH have a lower level of Hb before KTx and a higher level of Hb increase in the early postoperative period following KTx. LVMI and changes in LVEF and LAEVI have predictive value in absence of Hb increase in pediatric KTx recipients.